Simulation of local scour caused by submerged horizontal jets with Flow-3D numerical model - Mohammadali Mehnifard; Sadegh Dalfardi; Hossein Baghdadi; Zeinab Seirfar (Desert, 2015)
One of the most concerning issues for researchers is to predict the shape and dimensions of the scour pit nearhydraulic structures such as the base of bridges, weirs, valves and stilling basins due to both financial and humanhazards induced by destruction of the structure. As the scour issue has its own complexity in relation to themultiplicity of effecting factors on it, in this study therefore, the results of laboratory analysis of local scour due tosubmerged horizontal jets were compared with numerical simulation results from Flow-3D three-dimensional modelto test the potency of the numerical model. As a result, the model is proposed in place of the experimental modelwhich has its own drawbacks and high costs. In this study, we measure maximum scour depth in relative equilibriumin 2 states and 6 test modes with different valve openings and tail water depth per different discharges. Comparisonof the results indicates about 11% error for Flow-3D numerical model in relation to the experimental model which byconsidering the complexity of scour and deposition phenomena, is considered a good result.